2022
DOI: 10.1177/00420980221094700
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for a new municipalism: Public–common partnerships against the new enclosures

Abstract: This article considers the potential of public–common partnerships (PCPs) to act as a new municipalist intervention against the privatisation and financialisation of land in the UK. In previous publications, we have presented PCPs in abstract terms as a municipalist organisational form that could help communities eschew the disciplinary effects of finance capital to pursue alternative democratic forms of urban development. Here, we start to examine what this process looks like in practice. The article draws fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…In the UK, varieties of municipal entrepreneurship have been classified according to their relative progressive credentials: from ‘municipal financialisation’, through ‘progressive interventionism’ and ‘social innovation’, to ‘progressive self‐organisation’ (Barnett et al, 2022). Whilst plenty of attention has been directed at the extremes, at municipal financialisation (Beswick & Penny, 2018; Christophers, 2019; Penny, 2022; Pike, forthcoming; Pike et al, 2019) and progressive self‐organisation (Russell, Milburn, & Heron, 2022; Thompson, 2021)—arguably the most regressive and progressive tendencies, respectively—far less has been given to the ambiguous centre‐ground, the inflection point around which progressive and regressive trajectories pivot. If the concept of ‘entrepreneurial municipalism’ (Thompson et al, 2020) is a first cut at marking this inflection point between more speculative/extractivist and more generative/sustainable practices, this article explored the contours of the latter's variegated landscape.…”
Section: The Return Of British Municipal Radicalism?mentioning
confidence: 99%
“…In the UK, varieties of municipal entrepreneurship have been classified according to their relative progressive credentials: from ‘municipal financialisation’, through ‘progressive interventionism’ and ‘social innovation’, to ‘progressive self‐organisation’ (Barnett et al, 2022). Whilst plenty of attention has been directed at the extremes, at municipal financialisation (Beswick & Penny, 2018; Christophers, 2019; Penny, 2022; Pike, forthcoming; Pike et al, 2019) and progressive self‐organisation (Russell, Milburn, & Heron, 2022; Thompson, 2021)—arguably the most regressive and progressive tendencies, respectively—far less has been given to the ambiguous centre‐ground, the inflection point around which progressive and regressive trajectories pivot. If the concept of ‘entrepreneurial municipalism’ (Thompson et al, 2020) is a first cut at marking this inflection point between more speculative/extractivist and more generative/sustainable practices, this article explored the contours of the latter's variegated landscape.…”
Section: The Return Of British Municipal Radicalism?mentioning
confidence: 99%
“…A partial answer to this problem lies in the building of a new moral economy (Sayer, 2000) – the production of a new subjectivity or common-sense and the concomitant emergence of radical forms of citizenship – and its intersection with a material foundation. Suffice to say this helps makes sense of the claim that the ‘foundational renewal problem is about centralised, top-down policymaking as much as it is about the wrong policies’ (Foundational Economy Collective, 2018: 126) and that efforts to develop a new paradigm come with the ‘need to reinvent democratic politics and empower the regional and local’ (Bentham et al, 2013: 20).…”
Section: Intersectionsmentioning
confidence: 99%
“…Whilst social licensing can be thought of in place-based terms (such as the conditionalities put on a particular supermarket franchise and mediated through a local authority), place-based approaches tend to refer to socially innovative approaches to the ownership and governance of resources, networks and services. These might include a diversity of models such as public-common partnerships (Russell andMilburn, 2018, 2021;Russell et al, 2022), 'new foundational infrastructures' such as Long-Term Care Centres (Autonomy/LABORA, 2019: 33), and innovative forms of 'entrepreneurial municipalism' (Thompson et al, 2020a). These proposals all share the hypothesis that 'radical change is only likely to come through a new politics of foundational alliance involving hybrid organisations with regional/local government, intermediary organisations and businesses working together' and that 'such alliances are easiest to put together on a local basis' (FE Collective, 2018: 155).…”
Section: Social Innovationmentioning
confidence: 99%
“…In the context of urban austerity (Bayirbag et al 2017;Peck 2012), and in parallel to stories of municipal entrepreneurialism (Beswick and Penny 2018;Fuller 2018), the possibilities of "progressive localism" (Featherstone et al 2012) have become a focus of renewed attention within the United Kingdom and beyond, sometimes captured in the notion of the "new municipalism" (Featherstone et al 2020). Community wealth building (Power and Goodwin 2021) and public-common partnerships (Russell et al 2022) have been identified as providing a base for local initiative capable of delivering transformative economic and political change. There is a tension within these discussions (sometimes explicit, sometimes implicit) between approaches that start from initiatives sponsored through local government or the local state and those that are centred on mutualism and self-activity.…”
Section: Introductionmentioning
confidence: 99%
“…Community wealth building (Power and Goodwin 2021) and public–common partnerships (Russell et al. 2022) have been identified as providing a base for local initiative capable of delivering transformative economic and political change. There is a tension within these discussions (sometimes explicit, sometimes implicit) between approaches that start from initiatives sponsored through local government or the local state and those that are centred on mutualism and self‐activity.…”
Section: Introductionmentioning
confidence: 99%